Prediction of the skin sensitization potential of didecyldimethylammonium chloride and 3, 7-dimethyl-2, 6-octadienal and mixtures of these compounds with the excipient ethylene glycol through the human Cell Line Activation Test and the Direct Peptide Reactivity Assay. (August 2019) - Lee, JaeHee; Cho, AhRang; Gautam, Ravi; Kim, YeonGyeong; Shin, SoJung; Song, EunSeob; Kim, HyeonJi; Yang, SuJeong; Acharya, Manju; Jo, JiHoon; Maharjan, Anju; Shim, IlSeob; et al.
In commercial products such as household deodorants or biocides, didecyldimethylammonium chloride (DDAC) often serves as an antimicrobial agent, citral serves as a fragrance agent, and the excipient ethylene glycol (EG) is used to dissolve the active ingredients. The skin sensitization (SS) potentials of each of these substances are still being debated. Moreover, mixtures of DDAC or citral with EG have not been evaluated for SS potency. The in vitro alternative assay called human Cell Line Activation Test (h-CLAT) and Direct Peptide Reactivity Assay (DPRA) served to address these issues. On three independent runs of h-CLAT, DDAC and citral were predicted to be sensitizers while EG was predicted to be a non-sensitizer and also by the DPRA. Mixtures of DDAC or citral with EG at ratios of 7:3 and 1:4 w/v were all positive by the h-CLAT in terms of SS potential but SS potency was mitigated as the proportion of EG increased. Citral and its EG mixtures were all positive but DDAC and its EG mixtures were all negative by the DPRA, indicating that the DPRA method is not suitable for chemicals with pro-hapten characteristics. Since humans can be occupationally or environmentally exposed to mixtures of excipients with active ingredients, the present study may give insights into further investigations of the SS potentials of various chemical mixtures.